First records of the genus Seiria (Peyssonneliales, Rhodophyta) in the western Pacific with descriptions of three new species - Mills, Matthew S.; Schils, Tom (Phytotaxa, 2026)
The red algal genus Seiria (order Peyssonneliales) is newly reported from the western Pacific based on collections from Guam, Japan, and Kosrae. Three new species are described based on morphological observations and molecular analyses: Seiria guamensis sp. nov., S. japonica sp. nov., and S. kosraeana sp. nov. All species are attached by unicellular rhizoids, the only vegetative feature shared among all known species of the genus. Seiria japonica sp. nov. and S. kosraeana sp. nov. produce serially arranged tetrasporangia characteristic of the genus, whereas the examined specimen of S. guamensis sp. nov. was not reproductive. The three new species are distinguished from one another and from their congeners by unique combinations of morphological traits and by significant sequence divergence in COI-5P and rbcL molecular markers. Seiria and other peyssonnelioid algae are severely under-reported globally, underscoring the need for expanded collections to reveal their true diversity.